SPE Annual Technical Conference and Exhibition 2015
DOI: 10.2118/175108-ms
|View full text |Cite
|
Sign up to set email alerts
|

Miscible CO2 Water-Alternating-Gas (CO2-WAG) Injection in a Tight Oil Formation

Abstract: In this paper, miscible CO 2 water-alternating-gas (CO 2 -WAG) injection in the Bakken formation is experimentally studied and optimized. First, tight sandstone reservoir rock samples from the Bakken formation are characterized. Second, the saturation pressure, oil-swelling factor, CO 2 solubility, CO 2saturated Bakken light crude oil density and viscosity are measured. Third, the vanishing interfacial tension (VIT) technique is applied to determine the minimum miscibility pressure (MMP) of the Bakken light cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…The molecular weight of the Bakken light crude oil was measured to be 168.0 g/mol by using an automatic high‐sensitivity wide‐range cryoscopy (Model 5009, Precision Systems Inc., USA). The compositional analysis result of the cleaned light crude oil was obtained by using the standard ASTM D86 method and can be found elsewhere . The molar percentages of C 1–10 , C 11–20 , C 21–30 , and C 31+ were found to be 64.19, 26.94, 6.26, and 2.61 mol%, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The molecular weight of the Bakken light crude oil was measured to be 168.0 g/mol by using an automatic high‐sensitivity wide‐range cryoscopy (Model 5009, Precision Systems Inc., USA). The compositional analysis result of the cleaned light crude oil was obtained by using the standard ASTM D86 method and can be found elsewhere . The molar percentages of C 1–10 , C 11–20 , C 21–30 , and C 31+ were found to be 64.19, 26.94, 6.26, and 2.61 mol%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The oil‐swelling factor of the Bakken light crude oil‐CO 2 system at a given P eq and T res = 56.0 °C was measured by using a DBR PVT system (PVT‐0150‐100‐200‐316‐155, DBR, Canada). The detailed experimental setup and procedure for the oil‐swelling factor measurements were described in the previous study . Here, the Bakken light crude oil‐swelling factor f s is defined as the ratio of the CO 2 ‐saturated light crude oil volume at P eq and T res to the dead light crude oil volume at P a = 1 atm and T res .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Domestic and foreign scholars have found that the primary recovery rate of tight oil reservoirs obtained by hydraulic fracturing is generally low, and the oil well production decreases rapidly after 1 year (Baihly et al, 2010;Zhang et al, 2015;Rodriguez and Maldonado, 2019). Most reservoirs need to supplement formation energy by water injection or gas injection, but tight reservoirs often encounter problems such as injection difficulties or insufficient surrounding gas sources (Chen and Reynolds, 2015;Han and Gu, 2015). Therefore, how to effectively replenish formation energy is of great significance for improving recovery efficiency of tight oil reservoirs.…”
Section: Introductionmentioning
confidence: 99%